Market Orientation and Supply Chain Integration in Digital Coffee Shop Service - Rr. Pratistha Febyanti, Darjat Sudrajat, Teti Rohayati (Journal of Educational Studies, 2025)
The growing coffee consumption culture in urban society and the increasing use of digital platforms have changed how coffee shops identify customer demand, manage inventory, and maintain service consistency. In this context, supply chain performance has become an essential managerial concern because coffee shop businesses must respond to fluctuating demand, short product life cycles, intense competition, and customer expectations for fast and reliable service. This study aims to examine the effect of market orientation on supply chain performance, with supply chain integration as a mediating variable. This research employed a quantitative explanatory approach using survey data collected from coffee shop owners or managers in Jabodetabek. The respondents were selected through purposive sampling, resulting in 66 coffee shops that met the research criteria. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings show that market orientation positively affects supply chain integration and supply chain performance. Supply chain integration also improves supply chain performance and partially mediates the relationship between market orientation and supply chain performance. These findings indicate that market orientation is not merely a marketing activity, but also a managerial capability to interpret changes in urban digital consumer behavior and translate them into operational coordination, procurement, inventory management, and supplier collaboration. The study implies that coffee shop managers should integrate digital market insights with supply chain practices to maintain product availability, freshness, service speed, and service consistency.